A Bayesian approach to attribute based consideration sets - Gilbride, Timothy J. (Henry Stewart Talks, 2010)
The consumer decision problem and two stage decision rules, Discrete choice models and consideration sets, Using data augmentation and MCMC methods to model consideration sets, Alternative screening rules and how to operationalize them, An empirical application, Summary and extensions